Meta-analysis of Glutamine on Immune Function and Post-Operative Complications of Patients With Colorectal Cancer - Yang, Tao; Yan, Xuhong; Cao, Yibo; Bao, Tiantian; Li, Guangsong; Gu, Shengliang; Xiong, Kai; Xiao, Tianbao (Frontiers in Nutrition, 2021)
The aim of this meta-analysis was to evaluate the clinical significance of glutamine in the management of colorectal cancer (CRC) patients after radical operation. Electronic databases, including PubMed, EMBASE, MEDLINE and Cochrane Library, Chinese Biomedical Database (CBM), China National Knowledge Infrastructure (CNKI), VIP medicine information system (VIP) and Wanfang electronic databases were comprehensively searched from inception to 30, July 2021. Prospective randomized trials with glutamine vs. routine nutrition or blank therapy were selected. The immune function related indicators (including IgA, IgG, IgM, CD4+, CD8+ and the ratio of CD4+/CD8+) , postoperative complications (including surgical site infection [SSI], anastomotic leakage and length of hospital stay [LOS]) and corresponding 95% confidence intervals (CIs) were assessed in the pooled analysis. Subsequently, the heterogeneity between studies, sensitivity, publication bias and meta-regression analysis were performed. Consequently, 31 studies, which contained 2201 patients (1108 in glutamine group and 1093 in control group) were included. Results of pooled analysis indicated that glutamine significantly improved the humoral immune function indicators (including IgA [SMD = 1.15, 95% CI: 0.72 to 1.58], IgM [SMD = 0.68, 95% CI: 0.48 to 0.89], IgG [SMD = 1.10, 95% CI: 0.70 to 1.50]) and the T cell immune function indicators (including CD4+ [SMD = 0.76, 95% CI: 0.53 to 0.99], the ratio of CD4+/CD8+ [SMD = 0.92, 95% CI: 0.57 to 1.28]). Meanwhile, the content of CD8+ was decreased significantly (SMD = -0.50, 95% CI: -0.91 to -0.10) followed by glutamine intervention. Pooled analysis of SSI (RR= 0.48, 95% CI: 0.30 to 0.75), anastomotic leakage (RR= 0.23, 95% CI: 0.09 to 0.61) and LOS (SMD = -1.13, 95% CI: -1.68 to -0.58) were decreased significantly in glutamine group compared with control group. Meta-regression analysis revealed the covariate of small-sample effects influenced the robustness and reliability of IgG outcome potentially. Findings of the present study demonstrated that glutamine ought to be applied as an effective immunenutrition therapy in the treatment of CRC patients after radical surgery. The present meta-analysis has been registered in PROSPERO (no. CRD42021243327).